2022
DOI: 10.1158/1538-7445.sabcs21-p1-02-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-02-02: Examination of low Her2 expression in breast cancer

Abstract: Introduction: Antibody-drug conjugates (ADC) are designed to effectively deliver cytotoxic agents directly to malignant cells. Trastuzumab deruxtecan (Tdx), an ADC of trastuzumab, an enzyme-cleavable linker, and a cytotoxic topoisomerase I inhibitor, has been shown to have antitumor activity in patients with breast cancer with low levels of HER2. However, current companion diagnostic tests for HER2-targetting therapies, immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH), were optimized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The interobserver agreement between HER2 scores based on existing guidelines showed substantial concordance. This magnitude of concordance is in line with others’ reproducibility studies 16,31 . Schettini and colleagues showed that multi‐rater agreement was substantial, and almost half the discordant cases were between IHC score 0 versus IHC score 1+ 31 .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The interobserver agreement between HER2 scores based on existing guidelines showed substantial concordance. This magnitude of concordance is in line with others’ reproducibility studies 16,31 . Schettini and colleagues showed that multi‐rater agreement was substantial, and almost half the discordant cases were between IHC score 0 versus IHC score 1+ 31 .…”
Section: Discussionsupporting
confidence: 85%
“…Fernandez et al . demonstrated that the current standard assays utilised in the clinical setting do not efficiently differentiate IHC scores 0 or 1+ and only 26% of these cases had 90% concordance agreement 16 . Also, Schettini and colleagues showed that multi‐rater overall kappa score was 0.7, equivalent to substantial agreement, and almost half the discordant cases were between IHC score 0 versus 1+ 31 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations